Unraveling the Metabolomic Profile and Bioactivities of the Paratoid Gland Secretion from Rhinella granulosa - Barros, Elcio Daniel S.; Moncao Filho, Evaldo S.; Fonseca, Mariluce G.; Alves, Patricia S.; Santos, Antonia Laires S.; Feitosa, Chistiane M.; Silva, Dulce Helena S. [UNESP]; Costa, Pedro Mikael S.; Pessoa, Claudia; Campos, Carmem D. L.; Monteiro, Cristina A.; Chaves, Mariana Helena; et al. (Soc Brasileira Quimica, 2023)
Toads of the Rhinella genus have a pair of paratoid glands that store biological secretions of high toxicity and varied chemical composition, rich in biologically active compounds. The present work aimed to carry out the investigation of the metabolomic profile and evaluation of the biological potential of the secretion paratoid glands (PGS) from Rhinella granulosa. The paratoid secretion was collected in the Piaui state (Brazil), extracted with methanol and the extract was analyzed by ultra-performance liquid chromatography with quadrupole time-of-flight mass spectrometry. Fifty chemical constituents were identified. The extract showed cytotoxicity against tumor cell lines of the central nervous system (half maximal inhibitory concentration (IC50) = 1.9 mu g mL-1) and prostate (IC50 = 1.6 mu g mL-1), unsatisfactory antimicrobial potential (minimal inhibitory concentration (MIC) > 312 mu g mL-1) and inhibited the enzyme acetylcholinesterase (IC50 = 5.119 mg mL-1). The results presented relevant information about the PGS and contributed to the understanding of the metabolomic and biological potential of R. granulosa.
Keywords: Rhinella granulosa; toad secretion; UPLC-QToF-MS; MS; fingerprint; biological activities